2020
DOI: 10.1002/app.50425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the elastomer viscosity on the morphology and impact behavior of injection molded foams based on blends of polypropylene and polyolefin elastomers

Abstract: The impact resistance of injection‐molded polypropylene (PP) parts is severely reduced when they are foamed. It is necessary to implement strategies, such as elastomer toughening, to increase the impact behavior of foamed parts. However, the knowledge on the effect of elastomer addition on the morphology, cellular structure, and impact of injection‐molded cellular parts is very limited. In this work, foamed parts based on blends of PP and polyolefin elastomers have been produced and characterized. A high and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
(122 reference statements)
0
14
0
Order By: Relevance
“…Generally, it can be modified by introducing long‐chain branching, [ 10–13 ] crosslinking, [ 14–17 ] blending, [ 18–24 ] and inorganic filling, [ 25,26 ] and so forth, to improve the melt strength of PP and obtain foam with a better cell structure. Stange et al compared the effect of rheological properties of PP with different molecular structures on the foaming performance and found that the expansion ratio of HMS‐PP with a long‐chain branching was larger than that of linear PP.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it can be modified by introducing long‐chain branching, [ 10–13 ] crosslinking, [ 14–17 ] blending, [ 18–24 ] and inorganic filling, [ 25,26 ] and so forth, to improve the melt strength of PP and obtain foam with a better cell structure. Stange et al compared the effect of rheological properties of PP with different molecular structures on the foaming performance and found that the expansion ratio of HMS‐PP with a long‐chain branching was larger than that of linear PP.…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate selection of polymers/copolymers to blend with PP plays an important role in determining the final properties and applications 14 . It has been indicated that the impact strength of PP can be significantly improved by the combination with rubber phase such as ethylene‐propylene rubber, ethylene‐propylene‐diene rubber, ethylene–propylene‐styrene rubber as well as various olefin‐originated copolymers including ethylene‐propylene copolymer, ethylene‐vinyl acetate copolymer, styrene‐butadiene‐styrene, styrene‐ethylene‐butadiene‐styrene copolymers, and poly(ethylene‐octene) 4,15–18 . Moreover, the impact PP copolymers can be produced in a two‐reactor system to yield a homopolymer with an ethylene‐propylene rubber 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Intensive efforts on studies on the role of several factors such as processing parameters, 24,25 matrix nature (glass transition temperature, crystallinity degree), 25–27 and elastomer percentage 27,28 in achieving the final PP blended with elastomers have been made. Notwithstanding, the influences of the particle size of immiscible elastomers and the correspondence between PP microstructure and elastomer viscosity, on the impact response of the PP blends, are very limited 18,29 . Polyolefin‐based elastomers can be thermodynamically miscible or mechanically compatible.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations